Multi-dimensional carbon-based heat conduction enhanced microcapsule phase change composite material and preparation method thereof

By building a multi-dimensional carbon-based thermal conductivity network, the problems of low thermal conductivity and liquid leakage of traditional phase change materials are solved, and the phase change composite materials with high thermal conductivity and high thermal storage performance are achieved, which are suitable for spacecraft thermal management.

CN119859508AActive Publication Date: 2025-04-22XI AN JIAOTONG UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510069234.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-22
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The low thermal conductivity and liquid leakage of traditional phase change materials are difficult to meet the requirements of stable temperature in the internal thermal ambient temperature of the spacecraft.

Method used

The multi-dimensional thermal conductivity material composite filling strategy and multi-size scale graphite hybrid filler strategy are adopted to build a multi-dimensional carbon-based thermal conductivity network to improve the thermal conductivity of microcapsule phase-change composite materials and prevent liquid leakage.

Benefits of technology

It significantly improves the thermal conductivity of phase-change composite materials (up to 1.021W·m-1·K-1) and thermal storage properties (up to 81.540J·g-1) to meet the needs of spacecraft thermal management materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859508A_ABST
    Figure CN119859508A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-dimensional carbon-based heat conduction enhanced microcapsule phase change composite material and a preparation method thereof, and belongs to the technical field of phase change materials. Pitch-based carbon fibers (PCF), crystalline flake graphite (FG) and phase change microcapsules (PCMC) are used as raw materials to prepare the multi-dimensional carbon-based heat conduction enhanced microcapsule phase change composite material. A multi-dimensional carbon-based heat-conducting network is jointly constructed by adopting a multi-dimensional heat-conducting material synergistic doping and multi-scale crystalline flake graphite composite filling strategy, the heat conductivity of the microcapsule phase-change composite material is remarkably improved (can reach 1.021 W.m <-1 >. K <-1 >) through the generated heat-conducting synergistic enhancement effect, meanwhile, the high heat storage performance is kept (the phase-change enthalpy value can reach 81.540 J.g <-1 >), and the microcapsule phase-change composite material is suitable for being used as a heat-conducting material. And a theoretical basis and practical support are provided for design and application of a spacecraft thermal management material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of phase change materials, and in particular relates to a multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material and a preparation method thereof. Background Art

[0002] When performing high-precision scientific missions (such as space gravitational wave detection), tiny temperature fluctuations inside the spacecraft will seriously affect the precise measurement of gravitational waves, thereby affecting the reliability of the detection results. Traditional thermal management materials (such as organic phase change materials) have low thermal conductivity and are difficult to absorb the power consumption fluctuations generated by the internal equipment of the spacecraft in a timely manner. Therefore, they cannot meet the strict requirements of gravitational wave detection for the stability of the thermal environment temperature inside the spacecraft. Therefore, the development of thermal management materials with high thermal conductivity and high energy storage density has become a key research direction in the field of spacecraft thermal management.

[0003] As a typical organic solid-liquid phase change material, paraffin wax has the advantages of good thermal stability, non-toxicity, low cost, high phase change latent heat and low volatility. When the temperature rises, paraffin wax absorbs heat and inhibits further temperature rise; when the temperature drops, paraffin wax releases the stored heat to maintain the stability of the thermal environment temperature. However, the application of paraffin wax in spacecraft thermal management faces the following challenges: 1) Liquid leakage: Paraffin wax is prone to liquid leakage at temperatures above its melting point, resulting in a decrease in the material's heat storage capacity and cycle stability; 2) Low thermal conductivity: The thermal conductivity of paraffin wax is usually less than 0.3W / m·K, which limits the rapid transfer of heat inside the material and makes it difficult to absorb power consumption fluctuations inside the spacecraft in a timely manner. Therefore, preventing liquid leakage of paraffin wax, improving its thermal conductivity, and maintaining high heat storage performance have become key issues that need to be solved.

[0004] Phase change microcapsule (PCMC) technology provides an effective solution to the problem of liquid leakage. PCMC wraps paraffin with a shell material to prevent liquid leakage and improve cycle stability. However, the microcapsule shell material increases the interfacial thermal resistance and reduces the overall thermal conductivity of the phase change material. Summary of the invention

[0005] In order to solve the problems of low thermal conductivity and liquid leakage of traditional phase change materials, the present invention proposes a multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material and a preparation method thereof. The present invention adopts a multi-dimensional thermally conductive material compound filling strategy and a multi-size flake graphite hybrid filler strategy to jointly construct a multi-dimensional carbon-based thermal conductive network. The resulting thermal conductivity synergistic enhancement effect significantly improves the thermal conductivity of the microcapsule phase change composite material (up to 1.021W·m -1 ·K -1 ), while maintaining high heat storage performance (phase change enthalpy value can reach 81.540J·g -1), which provides theoretical basis and practical support for the design and application of spacecraft thermal management materials.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention:

[0008] The present invention provides a multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material, which is composed of the following raw materials in terms of mass percentage: 5% pitch carbon fiber (PCF), 5-25% flake graphite (FG), and the remainder phase change microcapsules (PCMC) (the total mass of phase change microcapsules, pitch carbon fiber and flake graphite is 100%).

[0009] The present invention uses PCF, FG and PCMC as raw materials to prepare a multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material. FG has high thermal conductivity, low density and excellent chemical stability due to its unique two-dimensional layered structure, and can form an efficient thermal conductive network in the phase change composite material, significantly improving the overall thermal conductivity of the phase change composite material. PCF has excellent thermal conductivity and mechanical strength, and its one-dimensional fiber structure helps to quickly transfer heat inside the phase change composite material.

[0010] Furthermore, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCF 5%, FG 25%, and PCMC 70%.

[0011] Furthermore, the PCMC is a core-shell structure, the core material is n-heptadecane, and the shell material is polymethyl methacrylate; and / or the average particle size of the PCMC is 5 μm.

[0012] Furthermore, the axial thermal conductivity of the pitch carbon fiber is 960 W·m -1 ·K -1 , radial thermal conductivity is 10W·m -1 ·K -1 .

[0013] Furthermore, the diameter of the pitch carbon fiber is 10 μm, the length is 25 mm, and the density is 2.23 g·cm -3 .

[0014] Furthermore, the thickness of the FG is 2 μm, and the diameter of the sheet is 10 to 100 μm.

[0015] Furthermore, the thickness of the FG is 2 μm, and the diameter of the sheet is 10 μm, 50 μm and / or 100 μm.

[0016] The size and distribution of high thermal conductivity materials are also crucial to improving thermal conductivity. The present invention effectively optimizes the thermal network of the phase change composite material by mixing thermal conductive materials of different sizes and adjusting the mixing ratio. Large-sized FG has a longer thermal conduction path and can form a continuous thermal conduction channel, while small-sized FG has a larger specific surface area and can build a denser thermal conduction network. Large-sized FG provides a long-distance thermal conduction path; medium-sized FG fills larger gaps to enhance the continuity of the thermal conduction network; small-sized FG fills tiny gaps to improve the density of the thermal conduction network. Therefore, by reasonably adjusting the mixing ratio of FG of different sizes, the continuity and density of the thermal conduction network can be taken into account to achieve the best thermal conduction effect.

[0017] Furthermore, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCF 5%, FG 4.25-12.5% ​​with a sheet diameter of 10 μm, FG 4.25-12.5% ​​with a sheet diameter of 50 μm, FG 0-16.5% with a sheet diameter of 100 μm, and the remainder is PCMC. The thickness of FG is 2 μm.

[0018] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCF 5%, FG with a sheet diameter of 10 μm 4.25%, FG with a sheet diameter of 50 μm 4.25%, FG with a sheet diameter of 100 μm 16.5%, PCMC 70%, and the thickness of FG is 2 μm.

[0019] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 70%, PCF 5%, FG 4.25% with a sheet diameter of 10 μm, FG 8.25% with a sheet diameter of 50 μm, FG 12.5% ​​with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0020] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 70%, PCF 5%, FG 4.25% with a sheet diameter of 10 μm, FG 12.5% ​​with a sheet diameter of 50 μm, FG 8.25% with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0021] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 70%, PCF 5%, FG 8.25% with a sheet diameter of 10 μm, FG 12.5% ​​with a sheet diameter of 50 μm, FG 4.25% with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0022] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 70%, PCF 5%, FG 12.5% ​​with a sheet diameter of 10 μm, FG 4.25% with a sheet diameter of 50 μm, FG 8.25% with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0023] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 70%, PCF 5%, FG 12.5% ​​with a sheet diameter of 10 μm, FG 8.25% with a sheet diameter of 50 μm, FG 4.25% with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0024] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 80%, PCF 5%, FG 4.95% with a sheet diameter of 10 μm, FG 4.95% with a sheet diameter of 50 μm, FG 5.1% with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0025] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 90%, PCF 5%, FG 1.65% with a sheet diameter of 10 μm, FG 1.65% with a sheet diameter of 50 μm, FG 1.7% with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0026] Exemplarily, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 70%, PCF 5%, FG 12.5% ​​with a sheet diameter of 10 μm, FG 12.5% ​​with a sheet diameter of 50 μm, and the thickness of FG is 2 μm.

[0027] Preferably, the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is composed of the following raw materials in terms of mass percentage: PCMC 70%, PCF 5%, FG 8.25% with a sheet diameter of 10 μm, FG 8.25% with a sheet diameter of 50 μm, FG 8.5% with a sheet diameter of 100 μm, and the thickness of FG is 2 μm.

[0028] The second technical solution of the present invention:

[0029] The present invention also provides a method for preparing the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material, comprising the following steps:

[0030] Accurately weigh each raw material according to mass percentage;

[0031] The phase change microcapsules are mixed with anhydrous ethanol, stirred to form a uniform suspension, flake graphite and pitch carbon fiber are added, and stirring is continued to ensure that the components are uniformly dispersed to obtain a mixture;

[0032] Drying the mixture to obtain a powder mixture;

[0033] The powder mixture is hot-pressed to obtain a multi-dimensional carbon-based thermally conductive enhanced microcapsule phase-change composite material.

[0034] Furthermore, the temperature of the hot pressing molding is 100° C., the pressure is 20 MPa, and the time is 6 hours.

[0035] Furthermore, after hot pressing, when the temperature dropped to room temperature, the pressure of 20 MPa was maintained for 4 h.

[0036] As a simple, efficient and low-cost method for preparing composite materials, the hot pressing process achieves dense molding of composite materials by promoting the interface bonding and densification of each phase material under controlled temperature and pressure conditions. Through this preparation process, PCMC, PCF and FG are effectively combined to construct a stable multi-dimensional thermal conductive network, thereby achieving the synergistic optimization between high thermal conductivity and high phase change enthalpy value of phase change composite materials. Therefore, the present invention adopts a hot pressing process to prepare a multi-dimensional carbon-based thermal conductive enhanced microcapsule phase change composite material, which effectively prevents the liquid leakage of paraffin and maintains high heat storage performance; at the same time, the synergistic thermal conductivity enhancement effect of the multi-dimensional carbon-based thermal conductive network significantly improves the thermal conductivity of the phase change composite material. Through experimental testing and finite element simulation, the effects of different material ratios and structures on the thermal properties (thermal conductivity, heat storage performance) of phase change composite materials are systematically studied, and the heat transfer mechanism of multi-dimensional carbon-based thermal conductive enhanced microcapsule phase change composite materials is explored, providing theoretical support for the design of spacecraft thermal management materials.

[0037] Furthermore, the preparation method of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is:

[0038] (1) Proportional weighing: Accurately weigh each raw material according to its mass fraction;

[0039] (2) Stirring and dispersing: PCMC was mixed with 500 mL of anhydrous ethanol and stirred for 20 min at a speed of 800 to 1000 rpm by mechanical stirring to form a uniform suspension, FG and PCF were added, and stirring was continued to ensure that the components were uniformly dispersed to obtain a mixture;

[0040] (3) Blast drying: The mixture is transferred to an electric blast drying oven and dried at 80° C. for 12 h to ensure that the anhydrous ethanol is completely volatilized and a uniform powder mixture is obtained; during the drying process, the sample is lightly shaken periodically to prevent powder agglomeration and improve the drying effect;

[0041] (4) Hot pressing: The dried powder mixture is placed in a molding mold and hot pressed at 100°C and 20 MPa using a hot press and maintained for 6 hours; after the temperature drops to room temperature, the pressure is maintained for 4 hours. The entire hot pressing process is carried out in a nitrogen environment to avoid material oxidation.

[0042] (5) Demolding and finishing: After demolding, the density is 1g·m -3 A rectangular sample with a size of 10 cm×10 cm×1.5 cm is prepared, and burrs are removed to obtain the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material.

[0043] The third technical solution of the present invention:

[0044] The present invention also provides application of the multi-dimensional carbon-based heat-conducting enhanced microcapsule phase-change composite material in spacecraft thermal management materials.

[0045] Compared with the prior art, the present invention has the following advantages and technical effects:

[0046] (1) PCMC content plays a key role in the balanced regulation of the thermal properties of the composite material. When the PCMC content is 70wt%, an efficient multidimensional carbon-based thermal conductive network is successfully constructed while maintaining a high phase change enthalpy value (81.282J·g -1 ), achieving the optimal balance between thermal conductivity and heat storage performance of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite materials.

[0047] (2) The composite filling strategy of multi-dimensional thermal conductive materials enhances the connectivity and density of the thermal conductive network. The one-dimensional thermal conductive path of PCF and the two-dimensional thermal conductive channel of FG are intertwined to synergistically construct a multi-dimensional carbon-based thermal conductive enhanced network, which significantly improves the thermal conductivity of the phase change composite material. Compared with the phase change composite material without PCF doping, the thermal conductivity of the PCF doped composite material increased by 153.4%, while the heat storage performance remained basically unchanged. Therefore, the composite filling of FG and PCF produces a synergistic thermal conductivity enhancement effect, shortens the heat transfer path, enhances the thermal response performance of the phase change composite material, and provides a strong guarantee for its thermal management during the heat absorption / release process.

[0048] (3) The multi-size FG hybrid filler strategy optimizes the thermal conductive network structure. By filling FG of different sizes, the thermal conductivity of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is significantly enhanced. Among them: large-size FG provides a long-distance thermal conductive path; medium-size FG fills larger gaps to enhance the continuity of the thermal conductive network; small-size FG fills tiny gaps to improve the density of the thermal conductive network. When the proportions of 10μm, 50μm and 100μm FG are 50wt%, 33wt% and 17wt% respectively (referring to the mass percentage of FG of different sizes in the total FG), the thermal conductivity of the phase change composite material reaches 1.021W·m -1 ·K -1 The phase change enthalpy is 81.540 J·g -1 Therefore, adopting a multi-sized FG hybrid filler strategy, especially increasing the content of small-sized FG, is a key measure to construct an efficient thermal conductive network. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0050] Figure 1 Schematic diagram of the preparation process of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite materials;

[0051] Figure 2 The SEM images of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material in Example 5, wherein (a) is 1 μm; (b) is 2 μm; (c) is 10 μm;

[0052] Figure 3 Schematic diagram of the RVE model of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material in Example 5;

[0053] Figure 4 DSC graphs of phase change composites with different PCMC contents;

[0054] Figure 5 are the thermal performance parameters of phase change composites with different PCMC contents;

[0055] Figure 6 Finite element analysis of thermal conductivity of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composites, including: (a) RVE temperature distribution with PCF; (b) RVE temperature distribution without PCF; (c) RVE heat flux density distribution with PCF; (d) RVE heat flux density distribution without PCF;

[0056] Figure 7 is the mixing ratio of FG of different sizes in samples 16 to 27;

[0057] Figure 8 Thermal performance parameters of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composites prepared with different FG mixing ratios in samples 16 to 27;

[0058] Fig. 9 Distribution diagram of equivalent thermal conductivity and heat flux density of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite materials prepared with different mixing ratios of FG (mass percentage), where: (a) 10μm FG accounts for 50%, 50μm FG accounts for 25%, and 100μm FG accounts for 25%; (b) 10μm FG accounts for 25%, 50μm FG accounts for 50%, and 100μm FG accounts for 25%; (c) 10μm FG accounts for 25%, 50μm FG accounts for 25%, and 100μm FG accounts for 50%. DETAILED DESCRIPTION

[0059] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0060] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0061] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0062] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0063] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0064] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0065] Unless otherwise specified, normal temperature and pressure in the present invention refers to 1 atmosphere (101.325 kPa), 25±2°C.

[0066] All raw materials used in the embodiments of the present invention are purchased from the market. As an example, phase change microcapsules (PCMC) were purchased from Hefei Xinneng Phase Change New Material Technology Co., Ltd., the core material is n-heptadecane, the shell material is polymethyl methacrylate, and the average particle size of PCMC is 5 μm; flake graphite (FG) was purchased from Forsman Technology (Beijing) Co., Ltd., the flake diameters are 10 μm, 50 μm and 100 μm, the thickness is 2 μm, and the density is 2.26 g·cm -3 , the in-plane thermal conductivity is 523 W·m -1 ·K -1 The thermal conductivity in the thickness direction is 38W·m -1 ·K -1 Pitch carbon fiber (PCF) was purchased from Forsman Technology (Beijing) Co., Ltd. with a diameter of 10 μm, a length of 25 mm, and a density of 2.23 g·cm -3 , axial thermal conductivity is 960W·m -1 ·K -1 , radial thermal conductivity is 10W·m -1 ·K -1 ; Anhydrous ethanol (analytical grade) was purchased from Shanghai Titan Technology Co., Ltd.

[0067] The performance testing method used in the present invention is as follows:

[0068] 1. Microscopic morphology characterization

[0069] A German Zeiss Sigma 300 scanning electron microscope (SEM) was used to characterize the microstructure of the multidimensional carbon-based thermally conductive enhanced microcapsule phase change composite material. The sample was fixed on the sample stage by conductive glue, the platinum (Pt) spraying time was 90s, and the test voltage was 3-15kV.

[0070] 2. Thermal conductivity test

[0071] Based on the transient plane heat source method, the thermal conductivity of the samples was tested using the TPS2500S thermal constant analyzer produced by Swedish HotDisk Company. A 5465 polyimide probe was used in the test process. The tested phase change composite samples were all 10 mm × 10 mm × 1 mm blocks.

[0072] 3. Heat storage performance test

[0073] The latent heat and phase transition temperature of the samples were measured using a German Netzsch 3500 Sirius differential scanning calorimeter (DSC) in a temperature range of -20 to 100 °C and a heating / cooling rate of 5 °C min -1 , nitrogen atmosphere.

[0074] The schematic diagram of the preparation process of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material of the present invention is shown in Figure 1 It should be pointed out that the parts not described in detail in the present invention are conventional operating methods in the art and are not the focus of the present invention. For example, specific methods such as mechanical processing to remove burrs are all completed using conventional methods.

[0075] The technical solution of the present invention is further illustrated by the following embodiments.

[0076] Example 1 to Example 11

[0077] The hot pressing process is used to promote the interface bonding and densification of each phase material under specific temperature and pressure conditions to prepare a multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material. The specific preparation steps are as follows:

[0078] (1) Proportional weighing: Each raw material was accurately weighed according to the mass fraction, and a total of 15 groups of samples (i.e., Examples 1 to 11, Comparative Examples 1 to 4) were prepared. The mass fraction and specific proportion of each component material are detailed in Tables 1 and 2. Samples 1 to 9 optimized the mixing ratio of FG of different sizes; Samples 10 to 12 were used as the control group of Samples 1 to 9, using only FG of a single size; Samples 13 and 14 were used as the control group of Sample 5, with PCMC contents of 80 wt% and 90 wt%, respectively; Sample 15 was used as the control group of Sample 5, containing only FG and PCMC, without adding PCF, wherein Samples 1 to 9 were Examples 1 to 9, Samples 10 to 12 were Comparative Examples 1 to 3, Samples 13 to 14 were Examples 10 and 11, respectively, and Sample 15 was Comparative Example 4.

[0079] (2) Stirring and dispersing: PCMC was mixed with 500 mL of anhydrous ethanol and stirred at 900 rpm for 20 min to form a uniform suspension. Then, FG and PCF were added and stirred continuously to ensure uniform dispersion of the various material components.

[0080] (3) Blast drying: The stirred mixture was transferred to an electric blast drying oven and dried at 80°C for 12 h to ensure that the anhydrous ethanol was completely volatilized and a uniform powder mixture was obtained. During the drying process, the sample was gently shaken periodically to prevent powder agglomeration and improve the drying effect;

[0081] (4) Hot pressing: The dried powder mixture is placed in a molding mold and hot pressed at 100°C and 20 MPa for 6 hours using a hot press. The temperature is then cooled to room temperature at a rate of 5°C / min and the pressure is maintained for 4 hours. The entire hot pressing process is carried out in a nitrogen environment to avoid oxidation of the material.

[0082] (5) Demolding and finishing: After demolding, the density is 1g·m -3 , a rectangular sample with a size of 10cm×10cm×1.5cm, and then the sample surface was mechanically processed to remove burrs to meet the performance test requirements.

[0083] Table 1 Mass fraction of each raw material of multidimensional carbon-based thermally conductive enhanced microcapsule phase change composites

[0084]

[0085]

[0086] Table 2 The quality of each raw material of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material

[0087]

[0088]

[0089] The microscopic morphology of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material (i.e., sample 5) prepared in Example 5 is as follows: Figure 2 As shown. Figure 2 As can be seen in (a), PCMC presents an irregular spherical structure, and its polymethyl methacrylate shell is intact, showing an excellent coating effect, effectively preventing microcapsule rupture and phase change material leakage. Figure 2 In (b) and (c), FG, with its two-dimensional layered structure, is tightly stacked with PCF under the hot pressing process to construct a complex multi-dimensional carbon-based thermal conductive network skeleton. In addition, PCMC is evenly coated on the surface of FG and PCF to ensure good interface bonding and compatibility between the components, effectively reducing the interface thermal resistance.

[0090] Based on the microscopic morphology characteristics of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material, the representative volume element (RVE) model of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material prepared in Example 5 was numerically reconstructed, as shown in FIG. Figure 3As shown. The finite element method was used to simulate the heat conduction process of phase change composites. To simplify the numerical model, the following assumptions were made: 1) FG is a regular hexagonal structure; 2) PCMC is completely filled in the multidimensional carbon-based network structure, and the interfaces are perfectly combined; 3) The PCMC-filled matrix is ​​a homogeneous material. The specific modeling steps are as follows:

[0091] (1) The random sequential adsorption (RSA) method is used to generate spatially randomly distributed FG and PCF according to the structural parameters, and the RVE model of the multidimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is numerically reconstructed.

[0092] (2) Temperature periodic boundary conditions are applied to the front, back, left, and right sides of the RVE model. The temperature and heat flux density of the boundary nodes are ensured to be continuous through multi-point constraint equations. The specific expression is:

[0093] T + -T - =T * (1)

[0094] Among them, T + and T - represents the temperature (K) of the periodic node set on the relatively parallel boundary of the positive and negative normal vectors of the RVE model, T * is the periodic temperature correction.

[0095] (3) Constant temperature boundary conditions are applied at the top and bottom of the RVE model: the top temperature is 300 K (hot end) and the bottom temperature is 273 K (cold end) to achieve unidirectional heat conduction.

[0096] (4) The RVE model was discretized using the Automatic method of the Abaqus finite element commercial software. The RVE model size was determined to be 25×10 -5 m, the grid size is 2×10 -6 m, ensuring that FG and PCF meet the design goals of random distribution, reducing the consumption of resources, and ensuring the accuracy of the calculation results.

[0097] In order to determine the basic thermophysical properties of the homogeneous matrix in the RVE model of multidimensional carbon-based thermally conductive enhanced microcapsule phase change composites, the Maxwell-Eucken model and Bruggeman model were used to calculate the thermal conductivity of single PCMC and PCMC-filled matrix.

[0098] PCMC has a core-shell structure, and its equivalent thermal conductivity can be calculated by the Maxwell-Eucken model:

[0099]

[0100] in, is the equivalent thermal conductivity of PCMC; core is the intrinsic thermal conductivity of the core (n-heptadecane), which is 0.197 W·m -1 ·K -1 ; shell is the intrinsic thermal conductivity of the shell (polymethyl methacrylate), which is 0.21 W·m -1 ·K -1 ;f core is the volume fraction of the core material, and the calculation formula is:

[0101]

[0102] Among them, d core is the core diameter of PCMC, which is 4.5 μm; d total is the total particle size of PCMC. The equivalent thermal conductivity of a single PCMC is calculated to be 0.198 W·m -1 ·K -1 .

[0103] Thermal conductivity of PCMC filled matrix

[0104] In the RVE model of multidimensional carbon-based thermally conductive enhanced microcapsule phase change composites, the homogeneous matrix is ​​regarded as a densely packed structure of PCMC. When PCMC is stacked in rhombohedral form, a cubic densest packed structure is formed, and its porosity calculation formula is:

[0105]

[0106] in, is the porosity of the matrix, and is calculated to be For PCMC filled matrix containing micropores, its equivalent thermal conductivity can be calculated using the Bruggeman model:

[0107]

[0108] Among them, λ matrix is the equivalent thermal conductivity of the matrix; air is the thermal conductivity of air (normal temperature and pressure), which is 0.026 W·m -1 ·K -1 ; The equivalent thermal conductivity of the PCMC filled matrix is ​​0.156 W·m -1 ·K -1 .

[0109] The DSC curves of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composites with PCMC contents of 70wt%, 80wt% and 90wt% are shown in Figure 4 As shown. The results show that the phase transition peak shapes of the three groups of samples (i.e., sample 5, sample 13 and sample 14) are basically the same, and all show multiple phase transition peaks, which correspond to the solid-solid phase transition process (monoclinic crystal to hexagonal crystal) and solid-liquid phase transition process of n-heptadecane in PCMC. At the same time, the phase transition temperatures of the three groups of samples (i.e., sample 5, sample 13 and sample 14) remain basically unchanged, with the phase transition temperature of the endothermic process being around 14.9°C and the phase transition temperature of the exothermic process being around 21.1°C.

[0110] The experimental test results of thermal conductivity (λ) and phase change enthalpy (ΔH) of phase change composites with different PCMC contents are shown in Figure 5 As shown. The results show that sample 14 (90wt% PCMC) has the highest ΔH, which indicates that n-heptadecane in PCMC provides a higher latent heat of phase change, so high content of PCMC significantly enhances the heat storage performance of the phase change composite material. However, the λ of sample 14 is only 0.591W·m· -1 ·K· -1 This is because the λ of PCMC is low. The high content of PCMC blocks the heat transfer path inside the phase change composite material, making it impossible to achieve efficient heat transfer. In contrast, the λ of sample 5 (70wt% PCMC) is as high as 0.887W·m -1 ·K -1 This is because as the PCMC content decreases, FG and PCF gradually form a multidimensional carbon-based thermal conductive network in the matrix, forming an efficient thermal conductive channel, which significantly improves the λ of the phase change composite material and shortens the thermal response time of the phase change material during the heat absorption / release process.

[0111] In order to achieve the best balance between thermal conductivity and phase change enthalpy, the thermal properties of phase change composite samples with different PCMC contents were analyzed and compared. The results show that the ΔH of sample 5 (70wt% PCMC) is 81.282 J·g -1 , compared with sample 14 (90wt% PCMC), it only decreased by 20.6%, while its λ increased by 50.1%, showing excellent thermal response characteristics (i.e., high thermal conductivity and high heat storage performance). Therefore, 70wt% PCMC was selected as the optimal component scheme for the subsequent preparation of phase change composites.

[0112] In order to study the effect of PCF on the thermal properties of microcapsule phase change composites, experimental tests of λ and ΔH were carried out on multidimensional carbon-based thermally conductive enhanced microcapsule phase change composites containing PCF and without PCF, as shown in Table 3. The results show that the λ of sample 5 (doped with 5wt% PCF) is significantly higher than that of sample 15 (without PCF), which is increased by 153.4%, indicating that the use of multidimensional thermal conductive material compound filling strategy significantly enhances the thermal conductivity of phase change composites, which is a key factor in building an efficient thermal conductive network. At the same time, the ΔH of sample 5 (81.282 J·g -1 ) and sample 15 (80.241 J·g -1 ), indicating that the introduction of PCF does not affect the dominant role of phase change microcapsules in thermal storage performance.

[0113] Table 3 Comparison of thermal performance parameters of phase change composites containing PCF and without PCF

[0114]

[0115] In order to reveal the enhancement mechanism of PCF on the thermal conductivity of phase change composites, RVE models of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composites with and without PCF were constructed, and the finite element method was used to simulate the heat conduction. Figure 6 (a) and (b) show the temperature gradient distribution of the RVE model. Figure 6 (c) shows that PCF forms a one-dimensional heat conduction path in the phase change composite material, which is intertwined with the two-dimensional heat conduction channel provided by FG, and synergistically constructs a multi-dimensional carbon-based heat conduction enhancement network. At the same time, the one-dimensional structure of PCF fills the interlayer gaps of FG, increasing the effective contact area between the thermal conductive material and the PCMC matrix, and improving the connectivity and stability of heat transfer inside the phase change composite material. In contrast, Figure 6 (d) shows that in the PCF-free phase change composite material, the heat conduction path mainly depends on the two-dimensional planar heat conduction channel formed by FG. Although the three-dimensional heat conduction network composed of two-dimensional planes connected to each other can achieve heat transfer, its heat conduction path is discontinuous, resulting in a significant decrease in the thermal response rate of the phase change composite material. Therefore, a multi-dimensional carbon-based heat conduction network skeleton was constructed by adopting a multi-dimensional thermal conductive material composite filling strategy. The synergistic thermal conductivity enhancement effect significantly shortened the heat transfer path, enhanced the thermal response performance of the phase change composite material, and provided a strong guarantee for its thermal management during the heat absorption / release process.

[0116] In order to study the effect of different sizes of FG (10μm, 50μm and 100μm) on the thermal properties of phase change composite materials, a three-factor three-level orthogonal experimental design was adopted, with the above three FG sizes as experimental factors, and each factor was set at low, medium and high levels. The mixing ratio of FG of different sizes in samples 16 to 24 (i.e., Examples 12 to 20) was determined, which helps to fully reveal the influence of the FG mixing ratio on the thermal properties of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite materials. Samples 25 to 27 (i.e., comparative examples 5 to 7) are used as the control group, which is composed of only a single size of FG. The mixing ratio of FG in each sample is, for example, Figure 7 In addition, the total content of FG in samples 16-24 (ie, examples 12-20) and samples 25-27 (ie, comparative examples 5-7) is 25wt%, the content of PCMC is 70wt%, and the content of PCF is 5wt%.

[0117] The experimental test results of λ and ΔH of samples 16 to 27 are as follows: Figure 8 The results show that the λ of sample 21 (containing 50% 10μm FG, 33% 50μm FG, and 17% 100μm FG) reaches the maximum value of 1.021W·m -1 ·K -1 , which is significantly higher than that of samples containing only a single size of FG (samples 25 to 27, whose λ is 0.923 W·m -1 ·K -1 , 0.835W·m -1 ·K -1 and 0.672W·m -1 ·K -1 ), the phase change enthalpy of sample 21 is the largest, which is 81.540 J / g, and the ΔH of samples 16 to 27 are basically the same. This shows that the multi-size FG hybrid filler strategy significantly improves the thermal conductivity of the phase change composite material without affecting its heat storage performance. The thermal conductive channel constructed by a single-size FG is insufficient in continuity and density, and FGs of different sizes play different roles in the thermal conductive network. Specifically: 1) Large-size FG (100μm) provides a long-distance in-plane thermal conductive channel, which can efficiently transfer heat, but large gaps are easily formed between FGs, resulting in discontinuous thermal conductive paths; 2) Medium-size FG (50μm) plays a bridging role, filling the gaps between large-size FGs and enhancing the continuity of the thermal conductive network; 3) Small-size FG (10μm) further fills the tiny gaps between large / medium-size FGs, increases the contact area between FGs, and improves the density of the thermal conductive network. Therefore, the synergistic effect of multi-sized FGs helps to build an efficient thermal conductive network, especially increasing the content of small-sized FG (10 μm) in the mixing ratio, which can significantly improve the thermal conductivity of phase change composites.

[0118] In order to further reveal the influence of the mixing ratio of FG of different sizes on the thermal conductivity of phase change composites and the formation mechanism of the thermal conductive network between FGs inside the material, the present invention constructed three RVE models of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composites. The mixing ratios of FG (mass percentage) are as follows: (a) 10μm FG accounts for 50%, 50μm FG accounts for 25%, and 100μm FG accounts for 25%; (b) 10μm FG accounts for 25%, 50μm FG accounts for 50%, and 100μm FG accounts for 25%; (c) 10μm FG accounts for 25%, 50μm FG accounts for 25%, and 100μm FG accounts for 50%. The finite element method was used to carry out heat conduction simulation analysis, and the heat flux density distribution of different RVE models is shown in the following figure. Fig. 9 As shown. The research results show that the thermal conductivity network in the RVE model (a) is more connected and the heat flux density distribution is more uniform, which is mainly attributed to the higher proportion of small-sized FG (10μm) in the RVE model (a), which effectively fills the gaps in the thermal conductivity path and increases the contact area between FGs of different sizes. In contrast, there is discontinuity in the heat flow path in the RVE models (b) and (c), and the thermal conductivity is poor. Therefore, the use of a multi-sized FG hybrid filler strategy, especially increasing the content of small-sized FG, is a key measure to construct an efficient thermal conductivity network. The synergistic enhancement of FGs of different sizes gives the multi-dimensional carbon-based skeleton a rapid thermal response characteristic, significantly improving the thermal conductivity of phase change composites.

[0119] In summary, the present invention prepared a multidimensional carbon-based thermally conductive enhanced microcapsule phase change composite material by hot pressing process, combined with experimental test and finite element simulation, studied the influence of material components on the thermal properties of the phase change composite material, revealed the formation mechanism of its internal multidimensional thermal conductive network, and obtained the following conclusions:

[0120] (1) PCMC content plays a key role in the balanced regulation of the thermal properties of the composite material. When the PCMC content is 70wt%, an efficient multidimensional carbon-based thermal conductive network is successfully constructed while maintaining a high phase change enthalpy value (81.282J·g -1 ), achieving the optimal balance between thermal conductivity and heat storage performance of multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite materials.

[0121] (2) The multi-dimensional thermal conductive material compound filling strategy enhances the connectivity and density of the thermal conductive network. The one-dimensional thermal conductive path of PCF and the two-dimensional thermal conductive channel of FG are intertwined to synergistically construct a multi-dimensional carbon-based thermal conductive enhanced network, which significantly improves the thermal conductivity of the phase change composite material. Compared with the phase change composite material without PCF doping, the thermal conductivity of the PCF doped composite material increased by 153.4%, while the heat storage performance remained basically unchanged (81.282 J·g -1). Therefore, the composite filling of FG and PCF produces a synergistic thermal conductivity enhancement effect, shortens the heat transfer path, enhances the thermal response performance of the phase change composite material, and provides a strong guarantee for its thermal management during the heat absorption / release process.

[0122] (3) The multi-size FG hybrid filler strategy optimizes the thermal conductive network structure. By filling FG of different sizes, the thermal conductivity of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material is significantly enhanced. Among them: large-size FG provides a long-distance thermal conductive path; medium-size FG fills larger gaps to enhance the continuity of the thermal conductive network; small-size FG fills tiny gaps to improve the density of the thermal conductive network. When the proportions of 10μm, 50μm and 100μm FG are 50wt%, 33wt% and 17wt% respectively (referring to the mass percentage of FG of different sizes in the total FG), the thermal conductivity of the phase change composite material reaches 1.021W·m -1 ·K -1 The phase change enthalpy is 81.540 J·g -1 Therefore, adopting a multi-sized FG hybrid filler strategy, especially increasing the content of small-sized FG, is a key measure to construct an efficient thermal conductive network.

[0123] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material, characterized in that: Calculated by mass percentage, it is composed of the following raw materials: 5% of asphalt carbon fiber, 5-25% of flake graphite, and the remainder is phase change microcapsules.

2. The multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to claim 1, characterized in that: Calculated by mass percentage, it is composed of the following raw materials: 5% asphalt carbon fiber, 25% flake graphite, and 70% phase change microcapsules.

3. The multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to claim 2, characterized in that: The phase-change microcapsules are of a core-shell structure, the core material is n-heptadecane, and the shell material is polymethyl methacrylate; and / or the average particle size of the phase-change microcapsules is 5 μm.

4. The multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to claim 2, characterized in that: The axial thermal conductivity of the pitch carbon fiber is 960 W·m -1 ·K -1 , radial thermal conductivity is 10W·m -1 ·K -1 .

5. The multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to claim 2, characterized in that: The flake graphite has a thickness of 2 μm and a flake diameter of 10 to 100 μm.

6. The multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to claim 5, characterized in that: The flake graphite has a thickness of 2 μm, and a flake diameter of 10 μm, 50 μm and / or 100 μm.

7. The multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to claim 2, characterized in that: Calculated by mass percentage, it is composed of the following raw materials: 5% asphalt carbon fiber, 4.25-12.5% ​​flake graphite with a flake diameter of 10μm, 4.25-12.5% ​​flake graphite with a flake diameter of 50μm, 0-16.5% flake graphite with a flake diameter of 100μm, and the remainder is phase change microcapsules. The thickness of the flake graphite is 2μm.

8. A method for preparing the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Accurately weigh each raw material according to mass percentage; The phase change microcapsules are mixed with anhydrous ethanol, stirred to form a uniform suspension, flake graphite and pitch carbon fiber are added, and stirring is continued to ensure that the components are uniformly dispersed to obtain a mixture; Drying the mixture to obtain a powder mixture; The powder mixture is hot-pressed to obtain the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material.

9. The method for preparing the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to claim 8, characterized in that: After hot pressing, when the temperature drops to room temperature, the pressure of 20 MPa is maintained for 4 h.

10. Use of the multi-dimensional carbon-based thermally conductive enhanced microcapsule phase change composite material according to any one of claims 1 to 7 in spacecraft thermal management materials.

Citation Information

Patent Citations

  • Preparing method for phase transited stored energy microcapsule covered with an organic polymer material

    CN101530772A

  • Embedded type phase-change energy storage microcapsule with enhanced heat conduction and preparation method of microcapsule

    CN104804711A

  • Heat conduction phase change composite material and preparation method thereof

    CN106479030A

  • Phase change material thin film as well as preparation method and application thereof

    CN109449131A

  • Phase change energy storage microcapsule applied to inorganic cementing material and preparation method of phase change energy storage microcapsule

    CN113355054A